Research Progress of Chloroquine and Hydroxychloroquine on the COVID-19 and Their Potential Risks in Clinic Use - Chen, Yan; Shen, TaiPeng; Zhong, LiJun; Liu, ZhiXi; Dong, XinWei; Huang, TingWenLi; Wang, QiuJu; Xiao, HongTao (Frontiers in Pharmacology, 2020)
In December 2019, a severe outbreak of a novel coronavirus (COVID-19) occurred in the whole world, posing a great threat to people's health. With the outbreak and development of the epidemic, how to improve the cure rate, find effective drugs against this virus, has been the most urgent problem. Chloroquine (CQ) was verified effective against COVID-19 in vitro. As CQ's analogue, hydroxychloroquine (HCQ) was also reminded as a potential candidate for treating COVID-19. This review summarizes the latest clinical trials of CQ and HCQ against COVID-19 and its therapeutic regimen in China aiming to share their current usage to the whole world and provide insight into its appropriate future use in the treatment of COVID-19. Through searching the CNKI and Wangfang databases in Chinese language and PubMed, EMBASE, and Ovid databases in English language to identify published reports with the keywords including "coronavirus/COVID, chloroquine, hyroxychloroquine" in alone or combined, we found out the potential preclinical or clinical evidence for using CQ and HCQ against COVID-19. Consequently, we also searched the website of Chinese Clinical Trial Registry (http://www.chictr.org.cn/) till the day on 27th, June, 2020. This review found that there are 23 programs aimed to treat the different phases under COVID-19 pipeline in clinic with CQ and HCQ, totally. The inclusion criteria, exclusion criteria and therapeutic regimen were all shared to consult. Among them, 7 have been canceled due to lack of patients or other objective factors. There are 2 trials have completed, which the potential relationship between usage and adverse reactions was discussed emphatically. Through literature research, we suggested that paid close attention to retinal toxicity and ophthalmologic adverse symptom of CQ and HCQ. And the outcome of HCQ in clinic shows better than CQ especially in protective effect with low dosage.